Characteristics and genesis of permian chert in the middle and upper Yangtze Region, China - Da-zhi Zhang; Jin-xiong Luo; Bin Feng; You-bin He; Zhan Wen (PLoS ONE, 2025)
Cherts, as chemical sedimentary formations, serve as repositories of historical evolutionary data encompassing paleotectonics, paleogeography, and paleoclimate. Furthermore, they play a crucial role as geological foundations for oil and gas exploration. In the Upper Yangtze region, the origin and underlying genesis mechanisms of unstratified cherts from the Permian period have been subject to ongoing debate. This study employs lithological analyses including outcrop profiles and thin-section observations alongside geochemical analyses of macronutrients, trace elements, and rare earth elements to investigate the depositional environment of laminated cherts from the Permian era. Additionally explored are the siliciclastic origins of non-laminated cherts and the diagenetic mechanisms at play in this area. The findings indicate that stratified chert in the Middle and Upper Yangtze regions originate from basin sedimentation below the carbonate compensation depth interface while unstratified chert primarily form through dissolution of carbonates attributable to both hydrothermal activity and seawater processes. This comprehensive investigation provides a robust geological foundation for oil and gas exploration within this study area while also serving as a valuable reference for future research on studies related to chert.